Effects of Plyometric Zig-Zag Run and Single Leg Speed Hop Exercises on Agility and Leg Muscles Explosive Power in Football Players - Fadhilah Ilmi, Dhiki; Wahyuni (Indonesian Journal of Medicine, 2024)
Background: Futsal is a ball game played by each of 5 people. With the aim of putting the ball into the opponent's goal. Agility and explosive power are required, plyometrics are used to increase lower body muscle power and increase explosive power by training muscles to perform more movements in a shorter time. This study aimed to determine the effects of plyometric zig-zag run and single leg speed hop exercises on increasing agility and leg muscle explosive power in futsal players. Subject and Method: This was a quasi experiments with no control group. The study was carried out in Kendal, Central Java, from May to June 2023. Total sample of 21 futsal players was selected simple random sampling. The dependent variable was leg muscle agility and explosive power. The independent variables were plyometric zig-zag run and single leg speed hop exercises. Leg muscle agility was measured using the agility t-test. Leg musce explosive power was measured using standing broad jump test. The data were tested using paired t-test. Result: Mean score of leg muscle agility after plyometric zig-zag run was faster (Mean= 9.86 sec.; SD= 0.58) than before (Mean= 10.03 sec.; SD= 0.53), p<0.001. Mean score of leg muscle explosive power after single leg speed hop exercises was higher (Mean= 217.05 cm; SD= 12.46) than before (Mean= 200.67 cm; SD= 10.89), p<0.001.Conclusion: Plyometric zig-zag run improves leg muscle agilty. Single leg speed hop exercises improves leg muscle explosive power. Keyword: exercise, plyometric, zig-zag run, single leg speed hop, agility, muscle explosive power